Sanitation and the Caste System in India. A tribute to B.R Ambedkar - Mariana Faiad Batista Alves (Geografares, 2022)
It is a particular fact of Indian society to manually clean latrines and septic tanks. Its practitioners, known as manual scavengers, mostly belong to the most vulnerable caste in society, the Dalits. The article seeks to relate the relevance of the legacy of anti-caste struggles fostered by B.R Ambedkar, relating the caste system to basic sanitation practices in the country. Ambedkar held a heated debate with Gandhi on the subject, and both presented different solutions to the question. In the 2000s, combating open defecation practices became a central part of social programs in the country. In 2014, the federal government launched the Clean India Mission, a social program aimed at universalizing access to toilets in the country. In this context, the article will move on to an analysis of the relationship between the caste system and current sanitary practices.
Keywords: India; caste; sanitation